Multifunctional III-nitride optoelectronic system on a tiny chip - Binju Wang; Jianwei Fu; Kang Fu; Ziqi Ye; Wenxuan Wu; Xumin Gao; Jiabin Yan; Yongjin Wang (AIP Advances)
Multi-quantum well (MQW) diodes exhibit simultaneous emission and detection, allowing them to serve as multifunctional devices, including light emitters, receivers, energy transmitters, and information transmitters. Leveraging this capability, we designed a Multifunctional Energy Transfer Information System (METIS) that integrates contactless control, energy harvesting, and information transfer. At the core of this system, the multifunctional energy communication chip operates effectively across a broad range of extreme temperatures and in various solution environments. As the ambient temperature varies from −60 to 120 °C, the peak emission wavelength shifts from 465 to 476 nm, and even with further temperature changes from −70 to 150 °C, the communication function remains stable. Encapsulated for durability, METIS functions reliably in extreme conditions such as ice, water, salt solutions, and other light-transmitting fluids without needing external circuitry. Additionally, we demonstrate passive control of analog switches via MQW diodes. The MQW diodes also enable contactless energy and optical information transfer, ensuring stable and controllable information reconstruction at the receiving end. This approach offers an innovative solution for energy and information transmission in extreme environments.